Komunikasi, Informasi, dan Edukasi Pada Keluarga Beresiko Stunting di Kecamatan Prabumulih Barat Kota Prabumulih - Lucyana Lucyana (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Stunting is one of the main health problems in Indonesia which is caused by various factors ranging from poor nutrition to unfavorable socio-economic conditions. This research aims to explore the effectiveness of the Communication, Information, and Education (KIE) program in efforts to reduce stunting rates in this region. The research method used is descriptive qualitative, with data collection through observation and document analysis. The research results show that the implementation of the IEC program has a significant role in increasing family knowledge and awareness regarding the importance of nutrition and health as well as child care. Target group data shows significant variations in the number of infants, toddlers, PUS, and pregnant PUS in various sub-districts and villages. These findings emphasize the importance of strategies tailored to the demographic conditions and specific needs of each region. This research concludes that an IEC program that is well designed and adapted to local needs can effectively help reduce stunting rates in West Prabumulih District. These findings provide recommendations for developing a more effective and holistic IEC strategy in efforts to deal with stunting in Indonesia